The Memory Discourse of the Holocaust in Hungary: Distortion of Memory - Vigneault, Sara-Jane (Cahiers d'histoire)

(untitled) (Cahiers d'histoire, 2022)
This article studies the memory of the Holocaust in Hungary and its distortion within the official narrative. This research, alternating between past and present, demonstrates the abyss between the “official” memory put forward by the Fidesz’s government, and the familial and personal memories. In line with Memory Studies, this research focuses on the past and historiography to underline the instrumentalization of the memory of the Shoah within the country. To conclude, the example of the monument of the German invasion at the Szabadság Tér (Liberty Square) in Budapest and its counter-memorial, Eleven Emlékmű (Living Memorial), are underlined to contrast “official” memory with personal and familial memories.